Computerization of sow feeding and estrous detection - tests under low-investment housing conditions in Kansas - R M Blair; David A Nichols; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1992)
In Exp. 1, weight change, backfat thickness, and litter size were compared for gilts fed individually or with a computer-controlled electronic sow feeder provided by Osborne Ind., Inc. and NEDAP-Poiesz, B.V. Twenty gilts were fed by each method, and no treatment effects were observed. In Exp. 2, electronic monitoring of visits to a boar were studied to evaluate the potential of the data to predict time of estrus. A very good correlation between boar visitation and estrous behavior was obtained. The data indicate that gilts can be fed with computercontrolled equipment under outside housing conditions in Kansas. Further, there is potential for developing a computer controlled system to electronically detect estrus in pigs.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Pig; Electronic feeding; Reproduction; Estrus